Internalizing Islamic Education through the Tablighi Jamaat Movement in Shaping the Religious Character of the Wetu Telu Indigenous Community of Bayan, Lombok - Sumiadi, Raden (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This research examines the process of internalizing Islamic education through the Jamaah Tabligh movement in shaping the religious character of the Wetu Telu indigenous community in Bayan, Lombok. The Wetu Telu community is an indigenous community with unique Islamic practices, blending local traditions with Islamic teachings. The presence of the Jamaah Tabligh movement, as a transnational da'wah (Islamic missionary) movement, has significantly influenced the transformation of religious understanding and practices among the local community. This research aims to analyze the da'wah strategies of Jamaah Tabligh in internalizing Islamic educational values, identify the dynamics of interaction between normative Islamic teachings and Wetu Telu local traditions, and evaluate the impact of the movement on the formation of the community's religious character. A qualitative approach using ethnographic methods was employed to collect data through participant observation, in-depth interviews, and document studies. The results show that Jamaah Tabligh applies a persuasive and cultural approach in the process of internalizing Islamic education, emphasizing practical worship, noble morals, and purification of faith. This internalization process faces challenges in the form of cultural resistance and concerns about the loss of local identity. However, cultural negotiation occurs, resulting in a synthesis between universal Islamic values and local wisdom. The impact of this movement is evident in increased awareness of worship, strengthening of community morals, and a gradual shift in religious practices towards a more orthodox understanding of Islam, although some members of the community still maintain elements of Wetu Telu tradition as part of their cultural identity.